In vitro bioaccessibility of Lutein and Zeaxanthin of yellow fleshed boiled potatoes - Burgos, G.; Munoa, L.P.; Sosa, P.; Bonierbale, Merideth W.; Felde, T. zum; Díaz, C. (Springer, 2013)
Yellow fleshed potatoes contain significant amounts of lutein and zeaxanthin but the bioaccessibility of potato carotenoids has not yet been investigated. The purpose of this study was to estimate the in vitro bioaccessibility of carotenoids provided by potato. Lutein and zeaxanthin concentrations of boiled, freeze dried and milled samples of seven yellow fleshed potato accessions were determined by HPLC before and after different steps (gastric, duodenal and micellar phase) of in vitro digestion. The gastric and duodenal digestive stability of lutein and zeaxanthin in boiled tubers of the different accessions ranged from 70 to 95 % while the efficiency of micellarization ranged from 33 to 71 % for lutein and from 51 to 71 % for zeaxanthin. For all accessions, amounts of lutein and zeaxanthin after micellarization were significantly lower than the original amount found in the boiled samples. The accession 701862 showed the highest bioaccessible lutein concentration (280 μg/100 g, FW) and the accessions 703566 and 704218 showed the highest bioaccessible zeaxanthin concentration (above 600 μg/100 g, FW). Considering the mean potato intake in the Andes (500 g per day), the accession 701862 provides 14 % of the lutein intake suggested for health benefits and the accessions 703566 and 704218 provide 50 % more than the suggested zeaxanthin intake.